2433. Evaluation of Meropenem (MEM) in Combination With Colistin (COL) Against Colistin-Resistant Extensively Drug-Resistant (XRD) Gram-Negative Bacteria. (26th November 2018) - Singh, Nivedita; Nguyen, Logan; Rybak, Michael J; Kaye, Keith S
Abstract: Background: The treatment of XDR Gram-negative bacilli poses a significant clinical challenge with limited treatment options. Colistin-resistant XRD Gram-negative bacteria are becoming more commonplace in the clinical setting. Combination therapy is resorted to for treatment of such strains. The objective of this in-vitro study was to evaluate the synergistic effect of the combination with COL and MEM against Colistin-resistant XDR Gram-negative bacilli. Methods: In this study, a total of 30 Colistin-resistant XDR Gram-negative clinical isolates were evaluated, including five isolates of Pseudomonas aeruginosa, twenty-four isolates of Acinetobacter baumannii and one isolate of Klebsiella pneumonia. Minimum inhibitory concentrations (MICs) were determined with COL and MEM for each strain by broth microdilution. COL and MEM MICs were measured in the presence of 0.25- to 0.5- × the MIC of the other antibiotic to determine the ability to lower MIC values. Time-kill assays were performed with each agent alone and in combination to evaluate the potential for synergistic interactions. Additive and synergistic effects were defined as 1- to 2-log10 and ≥ 2-log10 reductions in CFU/mL from the most active single agent at 24 hours, respectively. Results: All isolates were resistant to COL (MIC90 32 mg/L), whereas all bacteria with except one A. baumannii, were resistant to MEM (MIC90 >64 mg/L). Zero- to greater than nine-fold decrease in MEM MICs were observed in combination with COL at 0.25- to 0.5 × MIC. COL MICs decreased by 0 to >8-fold when combined with MEM. MEM plus COL demonstrated synergistic activity against 70% strains tested and additive in 3% of the tested strains at 24 h in time-kill. The combination was indifferent in 26% of the tested strains. Conclusion: These data indicate that the addition of MEM to COL therapy in colistin resistant XDR Gram-negative bacteria demonstrate synergistic or additive effects against a majority of XDR Gram-negative bacteria. The combination might be a promising therapeutic option for treatment of these problem pathogens. Disclosures: M. J. Rybak, Allergan: Consultant, Grant Investigator and Speaker's Bureau, Research grant and Research support. Achaogen: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Bayer: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Melinta: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Merck: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Theravance: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Sunovian: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. Zavante: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support. NIAID: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support.